Application of a ground-based, multi-channel microwave radiometer to the alerting of low-level windshear at an airport - P.W. Chan; Y.F. Lee (Meteorologische Zeitschrift, 2011)
Low-level windshear, which refers to sustained changes of headwind of 15 knots (7.7 m/s) or more over a distance of several hundred metres to about 4 km, could be hazardous to the aircraft flying close to the ground. This paper presents the preliminary results in the application of a radiometer in the alerting of low-level windshear. A ground-based, 14-channel microwave radiometer (7 oxygen channels and 7 water vapour channels) has been in use at the Hong Kong International Airport since May 2008. The radiometer data were mostly collected in clear and cloudy weather conditions without significant rainfall. Two approaches to the alerting of windshear have been studied, namely, the calculation of Brunt-Vaisala frequency and the standard deviation of the brightness temperature measured by a microwave radiometer at the 60 GHz oxygen absorption complex. The former tries to represent the stability of the boundary layer of the atmosphere (terrain-induced windshear tends to occur in stable boundary layer) and the latter tries to correlate the wind fluctuations with the temperature fluctuations. The performance of the windshear alerting rules so developed is studied by the relative operating characteristics (ROC) curve balancing the hit rate of pilot windshear reports and the alert duration. It turns out that the Brunt-Vaisala frequency does not show much skill in the alerting. On the other hand, the brightness temperature fluctuations are found to have skills in capturing the windshear. By combining the alerts from brightness temperature fluctuations with the existing alerts issued by the Doppler Light Detection And Ranging (LIDAR) system, it may be possible to fully automate the issuance windshear alerts for a runway corridor of the Hong Kong International Airport (HKIA) without the need of subjective windshear warnings issued by the aviation weather forecasters, at least for terrain-induced windshear. The probability of detection (POD) for pilot windshear report reaches 89 % with the percentage of time on alert of 20 %. The POD is only less than that for the existing overall windshear alerting service (machined generated windshear alerts plus windshear warnings issued by the aviation weather forecasters) by about 4 %.